El hijo de la novia - Campanella, Juan José, 1959- (Barcelona Filmax, 2002)
At age 42, Rafael Belvedere is having a crisis. He lives in the shadow of his father, he feels guilty about rarely visiting his aging mother, his ex-wife says he doesn't spend enough
Para todos los públicos
Idiomas : castellano. Subt. : castellano
Ricardo Darín, Héctor Alterio, Norma Aleandro
Keywords: Películas cinematográficas -- DVD